2017
DOI: 10.1503/cjs.005216
|View full text |Cite
|
Sign up to set email alerts
|

Thirteen-year wear rate comparison of highly crosslinked and conventional polyethylene in total hip arthroplasty: long-term follow-up of a prospective randomized controlled trial

Abstract: Thirteen-year wear rate comparison of highly crosslinked and conventional polyethylene in total hip arthroplasty: long-term follow-up of a prospective randomized controlled trial Background: The purpose of this study was to report the radiographic wear rates from a previous randomized controlled trial of first-generation highly crosslinked versus conventional polyethylene in total hip arthroplasty (THA) at a minimum of 13 years' follow-up. Methods:Patients returned for radiographic imaging and radiostereometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…However, the older conventional PE can be at risk. Our results are consistent with previously published studies indicating that the conventional PE has a higher wear rate than HXLPE, while the latter has a wear rate ranging from 0.002 to 0.15 mm/year and continues to be low even at long-term follow up (Engh et al 2012, Reynolds et al 2012, Babovic and Trousdale 2013, Glyn-Jones et al 2015, Teeter et al 2017, Tsukamoto et al 2017. Our 10-year follow-up RSA data indicates a lower risk of later osteolysis and aseptic loosening for HXLPE.…”
Section: Radiographysupporting
confidence: 91%
“…However, the older conventional PE can be at risk. Our results are consistent with previously published studies indicating that the conventional PE has a higher wear rate than HXLPE, while the latter has a wear rate ranging from 0.002 to 0.15 mm/year and continues to be low even at long-term follow up (Engh et al 2012, Reynolds et al 2012, Babovic and Trousdale 2013, Glyn-Jones et al 2015, Teeter et al 2017, Tsukamoto et al 2017. Our 10-year follow-up RSA data indicates a lower risk of later osteolysis and aseptic loosening for HXLPE.…”
Section: Radiographysupporting
confidence: 91%
“…This population typically is younger in addition to having a collection of anatomic and biomechanical considerations that historic implants and techniques were not equipped to handle. Many authors have demonstrated that HXLPE exhibits lower linear and volumetric wear rates, as well as a decreased rate of periprosthetic osteolysis, than older, conventional components [1417]. We hypothesize that contemporary implants with HXLPE, improved ingrowth surfaces, and increased modularity will continue to demonstrate decreased osteolysis and failure rates due to aseptic loosening; however, longitudinal study of the more recent cases in this series will be mandatory to confirm that premise.…”
Section: Discussionmentioning
confidence: 67%
“…Previously published studies investigating the bearing surface in primary THA showed that wear and cup migration in the first two years postoperative are good predictors of later THA failure [ 31 , 32 ]. The literature reports long-term wear rates of 0.04 ± 0.02 mm/year for highly cross-linked polyethylene liners versus wear rates of 0.08 ± 0.03 mm/year for conventional polyethylene [ 33 ]. These initial findings are not only useful for describing the mechanical properties of different PE liners, but are also of special clinical interest as a significant correlation was demonstrated between wear and reduced revision due to aseptic loosening and osteolysis [ 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%